2016
DOI: 10.1186/s12906-016-1154-5
|View full text |Cite
|
Sign up to set email alerts
|

High molecular weight of polysaccharides from Hericium erinaceus against amyloid beta-induced neurotoxicity

Abstract: BackgroundHericium erinaceus (HE) is a well-known mushroom in traditional Chinese food and medicine. HE extracts from the fruiting body and mycelia not only exhibit immunomodulatory, antimutagenic and antitumor activity but also have neuroprotective properties. Here, we purified HE polysaccharides (HEPS), composed of two high molecular weight polysaccharides (1.7 × 105 Da and 1.1 × 105 Da), and evaluated their protective effects on amyloid beta (Aβ)-induced neurotoxicity in rat pheochromocytoma PC12 cells.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…Consistent with previous studies [13], the present research clearly confirmed the neuroprotective effects of HE in cells and an AD mouse model, as demonstrated by a decrease in cell viability caused by strongly ameliorated neurotoxin, nuclear and mitochondrial apoptotic alternations, and abnormal behavior in mice. To our knowledge, this is the first confirmation of the neuroprotective effects of HE in l -Glu-induced DPC12 apoptotic cells, and a chemical drug ( d -gal and AlCl 3 )-induced AD mouse model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies [13], the present research clearly confirmed the neuroprotective effects of HE in cells and an AD mouse model, as demonstrated by a decrease in cell viability caused by strongly ameliorated neurotoxin, nuclear and mitochondrial apoptotic alternations, and abnormal behavior in mice. To our knowledge, this is the first confirmation of the neuroprotective effects of HE in l -Glu-induced DPC12 apoptotic cells, and a chemical drug ( d -gal and AlCl 3 )-induced AD mouse model.…”
Section: Discussionsupporting
confidence: 92%
“…Due to patients’ various biological responses, herbs and fungi have been applied as medicine or functional food for centuries, and as such have become a repository for biopharmaceutic development [1]. According to previous research, numerous polysaccharides extracted from fungus display neuroprotective properties [13]. Our group successfully isolated a polysaccharide from Sparassis crispa that protects DPC12 cells against l -glutamic acid ( l -Glu)-induced apoptosis via the mitochondrial apoptotic pathway [14].…”
Section: Introductionmentioning
confidence: 99%
“…S. baicalensis, H. erinaceus and R. rosea produce neuroprotective effects in models of Parkinson's disease (PD) [6,7,12,17,68,69], Alzheimer's disease (AD) [11,[70][71][72][73][74][75][76][77][78][79], Huntington disease (HD) [18], hypoxia/hypo-perfusion/stroke [51,80,81], nerve and brain injury [82,83], glutamate-induced neurotoxicity [16,75,84], and epilepsy [85][86][87]. The in vitro and in vivo neuroprotective effects of these herbal compounds, administered as either full/enriched herbal extracts and/or as single bioactive ingredients, are largely attributable to antioxidant, mitochondrial-protecting and anti-inflammatory activities ( Figure 2).…”
Section: Common Neuroprotective Effects Of S Baicalensis H Erinacementioning
confidence: 99%
“…Interestingly, in our study, the L. rhinocerus ME extract was observed to have potential neuroprotective effects in NSCs by attenuating DEX-induced apoptosis and cell nuclei apoptotic morphology. Several studies have described that extracts from other medicinal mushroom (e.g., Ganoderma lucidum and Hericium erinaceus) had antiapoptotic effects in neuronal cells [56][57][58][59]. The Active Hexose Correlated Compound (AHCC) isolated from extracts of different types of basidiomycetes was demonstrated to suppress DEX-induced apoptosis in rat thymocytes [60].…”
Section: Neuroprotective Effect Of L Rhinocerus Me Extract Against Dmentioning
confidence: 99%